SYSTEMATIC REVIEW AND META-ANALYSIS ON THE RISK OF NEONATAL MORALITY IN ANTENATAL CARE IN NIGERIA - Adehi , M.U; Alhaji, Ismailia Sulaiman; Idowu , Lawrence Ezekiel; Saleh , Ibrahim Musa (Top Journal of Public Policy and Administration (TJPPA), 2025)
Neonatal mortality is a major public health problem throughout the world, most notably in developing countries. There exist inconclusive findings on the systematic review and meta-analysis on the risk of neonatal mortality in antenatal care in Nigeria. Thus, the aim of this systematic review and meta-analysis was to reveal the pooled effect of antenatal care visits on the incidence of neonatal death. The effect size index was risk ratio and date was sourced via Pubmed, Science Direct, Web of Science, Medline, Research gate, and Google Scholar. The random-effects model was used for the analysis. The studies in the analysis were assumed to be random sample from a universe of antenatal care visits on neonatal mortality studies and. STATA/SE for windows version 13 software was used to calculate the pooled effect size with 95% confidence intervals (95% CI) of maternal antenatal care visits on neonatal death using the DerSimonian and Laird random effects meta-analysis (random effects model), and results were displayed using a forest plot. Statistical heterogeneity was assessed using the Cochran Q test (chi-squared statistic) and I2 test statistic and visual examination of the forest plot. A total of 12 studies were included in the meta-analysis. Cochran’s Q was 88.12 (df = 11, p=0.000), indicating significant heterogeneity. The relative excess in Q had a point estimate of 2.830 (95% CI: 1.232–4.450). The proportion of variability due to heterogeneity (I2) was 87.5% (95% CI: 34.1%–94.9%), further supporting the presence of substantial heterogeneity. The pooled effect estimate showed that antenatal care significantly reduced the risk of neonatal mortality, with an RR of 0.66 (95% CI: 0.56–0.75). This result indicates a 34% reduction in the risk of neonatal mortality with ANC compared with no or minimal care. The null hypothesis of no difference (RR=1) was rejected. The current systematic review and meta-analysis revealed that antenatal care visits were significantly associated with lower rates of neonatal death. The risk of neonatal death was significantly reduced by 34% among newborns delivered from mothers who had antenatal care visits. Thus, visiting antenatal care clinics during pregnancy is strongly recommended, especially in Nigeria. This meta-analysis provides robust evidence that antenatal care significantly reduces the risk of neonatal mortality. Despite the high heterogeneity, the findings underscore the critical importance of promoting ANC as a key strategy for improving neonatal survival. Future research should explore the sources of heterogeneity and examine the specific components of ANC that contribute to the observed benefits